Produktivitas dan pertumbuhan industri di Indonesia - Widarjono, Agus (Economic Journal of Emerging Markets, 2016)
An industrilization is a strategic effort to restructure economy and to change society's life because it can transform an agricultural society that is static to become an industrial society that is dinamic.